Petroglyphs-symbols of the Northern Balkhash Region in Kazakhstan (Antiquity and the Middle Ages) - Bedelbayeva, M.V.; Novozhenov, V.A.; Rogozhinsky, A.E.; Kaldybaeva, G.A. (МАИАСП, 2024)
The article is devoted to the analysis of petroglyphs-symbols founded in the figurative monuments of the Northern Balkhash Region and Betpakdala and having complex mythological content, which is repeated in the form of symbolic signs similar in iconography, found over vast geographical spaces. These include images of solar signs, labyrinths, lattices, as well as some animals, chariots, anthropomorphic characters and clan’s tamgas. The analogies proposed by the authors indicate the vast geography of their distribution and contacts of the local population with the southern regions of Central Asia both in the Bronze Age and in subsequent historical periods.
Keywords: Betpakdala; chariots; Schrenk’s tulip; sun-headed characters; solar signs; tamgas; migrations; sacred landscapes